Measuring adaptation progress across scales and time frames - Grosjean, Godefroy; Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Presentation on metrics for agriculture adaptation for the Agriculture Committee of the International Platfom for Adaptation Metrics (IPAM)